Political News Framing Approach at Detik.com: Analysis of the 2024 Presidential Election Results Dispute - Alwardah, Rivana; Dwitama, Izhhari Ichasul; Nugraha, Asep Sunandar (CV. Publikasi Indonesia, 2024)
This research aims to find out the analysis of framing (framing/packaging) political news in online media Detik.com regarding the news of the dispute hearing of the 2024 presidential election results. To answer this problem, the framing method of the Zhongdang Pan and Gerald M Kosicki model was used. This research is included in qualitative. The data analysis used in this study was media text analysis using the framing analysis method using the Zhong Dang Pan and Gerald M. Kosicki model approach. The reserch results show that detik.com, in reporting news uses the inverted pyramid technique. Where the main topic of discussion discussed in the news is stored at the beginning of the news. In addition, there are several data obtained by news writers from the statements of sources to be used as data sources. The news structure uses 5W+1H, and the source does not throw many quotes.